Do‐it‐yourself cement work: the main cause of severe irritant contact dermatitis requiring hospitalization. (20th August 2012) - Poppe, Heiko; Poppe, Lidia Marilia; Bröcker, Eva‐B.; Trautmann, Axel
<x xml:space="preserve">Abstract</x> Background. There are myriads of potentially irritant agents causing acute irritant contact dermatitis. In the large majority of cases, dermatitis is mild to moderate, and patients do not need hospitalization. However, some agents or special circumstances may cause severe dermatitis requiring more intensive therapy. Objectives. The aim of this study was to evaluate causative agents of severe acute irritant contact dermatitis requiring hospitalization. Methods. In this single‐centre observational cohort study, we included 54 consecutive patients presenting with signs and symptoms of acute irritant contact dermatitis for which hospitalization was necessary. The severity of dermatitis was graded (grade I–IV) according to intensity, and details related to the skin irritation (irritant agent, area of exposure, time interval to onset of symptoms, and duration of hospitalization) were determined. Results. All cases with severe ulcerative dermatitis (grade IV) were caused by wet cement, owing to prolonged skin contact. These cement burns are clearly associated with amateur work, younger age, male preponderance, and leg localization. Conclusions. The study data provide clear‐cut evidence that wet cement is a severely irritant substance that regularly causes the most severe form of acute irritant contact dermatitis. The main causative prerequisite for these cement burns is do‐it‐yourself work with poor protective measures.